Support System for Determination of Low-Income Students Scholarship (BSM) with Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) - Abdul Azis; Bagus Adhi Kusuma; Alfika Maselia (International Journal of Informatics and Information Systems, 2020)
Muhammadiyah 3 Middle School in Purwokerto is the school that organizes the Low-Income Students Scholarship (BSM) program every first semester held in each new school year. During this time, processing student data and other equipment have been processed with manual calculations, as well as data storage using only Microsoft Excel. In selecting ranking, it still uses paper. The paper calculation on the selection of BSM recipients in the previous year is often lost and hard to find already needed, also there is no particular system for processing the data so that the subjective method is still needed by relying trusts on personal. The purpose of this study is the creation of a Decision Support System (DSS) application for Determining Low-Income Students Scholarship (BSM) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method at Muhammadiyah 3 Middle School in Purwokerto so that the selection process of Low-Income Students Scholarship (BSM) can be used. So that it is right on target to students who are entitled to BSM and can store data safely. The system development method used is a waterfall.